Accesul populaţiei din România la utilităţile publice: consumul de energie - Stanciu, Mariana (Calitatea Vieții, 2006)
For about a quarter of the Romanian population, the acces to public utilities and use of energy is a real challenge. The ability of different consumer groups to pay for energy and why we should promote energy affordability in Romania are only some of the issues of this article.